Research on lifetime distribution and reliability of IGBT module based on accelerated life test and K-S test. (28th March 2019) - Wu, Huawei; Ye, Congjin; Zhang, Yuanjin; Hou, Fei; Nie, Jingquan
To realise lifetime distribution and reliability analysis of IGBT, a new research method for IGBT module lifetime was proposed based on double stress accelerated life test and K-S test. In this method, the lifetime of IGBT module was assumed to be logarithmic normal distribution. Then the K-S test was used to test the distribution of the logarithmic normal and Weibull on a set of the junction temperature and vibration double stress constant stress accelerated life test data of IGBT module for electric vehicle. And another set of IGBT accelerated life data was simulated and analysed by using the accelerated life test data analysis software. The results show that the lifetime of IGBT modules under ALTA accelerated life simulation is still confirmed to the lognormal distribution, which further validates the correctness of the proposed assumption. This method has certain guiding significance to the life distribution and reliability analysis of IGBT module.